Stopping power of dense plasmas: The collisional method and limitations of the dielectric formalism - Clauser, Cesar Fernando (2018)
We present a study of the stopping power of plasmas using two main approaches: the collisional (scattering theory) and the dielectric formalisms. In the former case, we use a semiclassical method based on quantum scattering theory. In the latter case, we use the full description given by the extension of the Lindhard dielectric function for plasmas of all degeneracies. We compare these two theories and show that the dielectric formalism has limitations when it is used for slow heavy ions or atoms in dense plasmas. We present a study of these limitations and show the regimes where the dielectric formalism can be used, with appropriate corrections to include the usual quantum and classical limits. On the other hand, the semiclassical method shows the correct behavior for all plasma conditions and projectile velocity and charge. We consider different models for the ion charge distributions, including bare and dressed ions as well as neutral atoms.